Eksplorasi Bentuk Tempurung Kura-Kura Alligator Snapping Dalam Karya Seni Rupa Kontemporer - Syeifty Syeifty; M. Dwi Marianto; Tri Septiana Kurniati (Student Research Journal, 2023)
Turtles are reptiles that have uniqueness and beauty, which radiates from the character of the shell, the beauty of color and shape, and the history of the turtle's life. The snapping alligator is an extraordinary beauty because it has the characteristics of a shell that is like a tapered and jagged hill. The problem discussed in this paper is how the character of the snapping alligator turtle shell is, as well as how to formulate and visualize this character in contemporary works of art. The final result of the process of creating this work, the author presents in the form of an alligator snapping turtle shell which has been changed based on the results of the exploration of the author's imagination. With this new form created, the author feels that he has found more freedom in creativity which is not only limited by conventional rules and rules that exist in realist form.